Epidemiology of neglected tropical diseases in transplant recipients: review of the literature and experience of a Brazilian HSCT center - Machado, Clarisse Martins; Martins, Talita Chaves; Colturato, Iago; Leite, Marília Souza; Simione, Anderson João; Souza, Mair Pedro de; Mauad, Marcos Augusto; Colturato, Vergílio Rensi (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
The rising success rate of solid organ (SOT) and haematopoietic stem cell transplantation (HSCT) and modern immunosuppression make transplants the first therapeutic option for many diseases affecting a considerable number of people worldwide. Consequently, developing countries have also grown their transplant programs and have started to face the impact of neglected tropical diseases (NTDs) in transplant recipients. We reviewed the literature data on the epidemiology of NTDs with greatest disease burden, which have affected transplant recipients in developing countries or may represent a threat to transplant recipients living in other regions. Tuberculosis, Leprosy, Chagas disease, Malaria, Leishmaniasis, Dengue, Yellow fever and Measles are the topics included in this review. In addition, we retrospectively revised the experience concerning the management of NTDs at the HSCT program of Amaral Carvalho Foundation, a public transplant program of the state of São Paulo, Brazil.